EFEKTIVITAS KOMUNIKASI GURU PENDAMPING PADA SISWA BERKEBUTUHAN KHUSUS MELALUI PENDIDIKAN INKLUSI DI SMPN 12 SURAKARTA - Buddy Riyanto, Bhekti Dwi Pangestu & (Transformasi, 2018)
Communication is on important thing in human life. Teacher and student communication have an important role for achieving good and effective learning goals. Communication between accompanying teacher and students SMPN 12 Surakarta is an inclusive school that receives student with special needs to follow the education in public school. From the explanation above, it was found the problem formulation of how the effectiveness of communication conducted by the accompanying teacher at SMPN 12 Surakarta to student with special needs, through inclusive education. The purpose of this study was to describe how the effective communication of accompanying teacher at SMPN 12 Surakarta to students with special need through inclusive education. The type of the research used in this study is descriptive research with qualitative research methods. The theory used is the opinin of Jalaludin Rakhmat (2011) which states that the effectiveness of communication is an effect in communication that will arise if there is a change in the perceived, liked, or hated. This effect is related to emotions, attitudes, effect on real behavior can be observed, in the form of action patterns, and changes in knowledge. The accompanying teacher communicates using clear and soft indonesian. The accompanying teacher motivated student with special needs so that the enthusiasm in attending the lesson and the accompanying teacher would simplify the material provided by the class teacher so that student with special needs easily understood the subject matter the result of the study explained that communication carried out by the accompanying teacher in improving the understanding of the material of students with special needs has been effectiveKeyword : communication effectiveness, accompanying teacher, student with special needs